2023
DOI: 10.3847/1538-3881/aced9a
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Composition of Planets in Single-planet and Multiplanet Systems Orbiting M dwarfs

Romy Rodríguez Martínez,
David V. Martin,
B. Scott Gaudi
et al.

Abstract: We investigate and compare the composition of M-dwarf planets in systems with only one known planet (“singles”) to those residing in multiplanet systems (“multis”) and the fundamental properties of their host stars. We restrict our analysis to planets with directly measured masses and radii, which comprise a total of 70 planets: 30 singles and 40 multis in 19 systems. We compare the bulk densities for the full sample, which includes planets ranging in size from 0.52 R ⊕ to 12.8 R … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 117 publications
3
8
0
Order By: Relevance
“…Figure 6 contains the same stellar sample, but separates the stars based on planet multiplicity. The [Fe/H] distributions of the two panels are qualitatively similar, although a slight bias toward lower metallicities appears to be present for the stars with multiple known planets, consistent with the findings of Anderson et al (2021) andRodríguez Martínez et al (2023). However, we again note that this figure contains stars with metallicities derived using a variety of methods, so this apparent tendency may not be significant.…”
Section: Stellar Metallicity and System Propertiessupporting
confidence: 78%
See 1 more Smart Citation
“…Figure 6 contains the same stellar sample, but separates the stars based on planet multiplicity. The [Fe/H] distributions of the two panels are qualitatively similar, although a slight bias toward lower metallicities appears to be present for the stars with multiple known planets, consistent with the findings of Anderson et al (2021) andRodríguez Martínez et al (2023). However, we again note that this figure contains stars with metallicities derived using a variety of methods, so this apparent tendency may not be significant.…”
Section: Stellar Metallicity and System Propertiessupporting
confidence: 78%
“…Anderson et al (2021) later found a similar trend as Brewer et al (2018) for M dwarfs and late K dwarfs using Gaia color as a proxy for metallicity, showing that compact multiplanet systems tend to be around cool stars that are significantly bluer (more metal-poor) than stars hosting only a single planet. In an independent analysis that utilized planet-hosting M dwarfs with photometrically and spectroscopically determined metallicities, Rodríguez Martínez et al (2023) also found a tendency for multiplanet systems to orbit more metal-poor M dwarfs than single-planet systems. As more planetary systems are discovered around these cool stars, having reliable metallicities will be crucial for similar population-level studies that aim to infer how this property influences planet formation and evolution around low-mass stars.…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence rate of Earth-like planets around M dwarfs in the Kepler sample is less than a few percent for short orbital periods P orb,0  1 day (Mulders et al 2015;Hsu et al 2020), where our models predict migration due to resonance locking. The story appears to be similar for TESS, as recent analyses find only a few planets with Earth-like radii at 1-day orbits out of the dozens of planets orbiting M dwarfs in their sample (Rodríguez Martínez et al 2023). The vast majority of planets lie at a orbits of a few to 10 days, where negligible migration occurs in our fully convective stellar models.…”
Section: Comparison With Observed Systemssupporting
confidence: 60%
“…constituent planets, indicating that these CKS samples lack the requisite associated planetary mass data for a population-level uniformity analysis. However, this dearth may be alleviated in part by the substantial efficacy with which the M-R bivariate behavior of small, rocky (R p 1.6 R ⊕ ) worlds may be modeled (see Figure 5 of Rodríguez Martínez et al 2023;Figure 8 of Rubenzahl et al 2024) by the semi-empirical M-R relation for Earth-like planets presented by Zeng et al (2016). We therefore utilize this Zeng et al (2016) Earth-composition model to robustly infer planetary masses M p for the 118 objects (across 48 systems) within our CKS rocky sample (Figure 3, gold curve and points).…”
Section: Inference Of Planetary Masses For Cks Rocky Systemsmentioning
confidence: 99%